2006
DOI: 10.1111/j.1745-7254.2006.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide ameliorates vascular calcification induced by vitamin D3 plus nicotine in rats1

Abstract: Aim: To investigate the role of the endogenous cystathionine γ-synthase (CSE)/ hydrogen sulfide (H 2 S) pathway in vascular calcification in vivo. Methods: A rat vascular calcification model was established by administration of vitamin D3 plus nicotine (VDN). The amount of CSE and osteopontin (OPN) mRNA was determined by using semi-quantitative reverse-transcription polymerase chain reaction. The calcium content, 45 Ca2+ accumulation and alkaline phosphatase (ALP) activity were measured. H 2 S production a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 38 publications
1
45
1
Order By: Relevance
“…Several animal studies reported that VDN treatment brought 5-to 10-fold increase of arterial Ca content to young male Sprague-Dawley (SD) rats (36,41,42). However, our data unexpectedly showed a slight increase but no significant difference in the arterial Ca content of the 0.6% Ca intake group in OVX with VDN rats compared with the 0.6% Ca intake group in OVX without VDN.…”
Section: Discussioncontrasting
confidence: 71%
“…Several animal studies reported that VDN treatment brought 5-to 10-fold increase of arterial Ca content to young male Sprague-Dawley (SD) rats (36,41,42). However, our data unexpectedly showed a slight increase but no significant difference in the arterial Ca content of the 0.6% Ca intake group in OVX with VDN rats compared with the 0.6% Ca intake group in OVX without VDN.…”
Section: Discussioncontrasting
confidence: 71%
“…The inconsistency between the results of previous studies and our results were presumably because of using different animal models for in vivo studies. VDN treatment reportedly results in an approximately 15-fold increase in arterial Ca levels in young male Wistar rats 8 wk of age (18)(19)(20)(21), whereas this treatment results in ,10-fold increase in arterial Ca levels in young male SD rats of various ages (22)(23)(24). In female rats, the investigation of the calcification paradox by means of OVX plus VDN treatment in vivo has not been studied, except in our previous studies with SD rats of 6 wk (7,25).…”
mentioning
confidence: 99%
“…Experimental angiosteosis induced by combined introduction of vitamin D and nicotine in rats is accompanied by a drop in the expression of CSE, the activity of the latter, and the level of H 2 S in tissues of the aortal wall. Exogenous H 2 S prevents the process of angiosteosis; this fact is confirmed by a decrease in the calcium concentration in the vessels and also by drops in the activity of acidic phosphatase and expression of osteopontin under conditions of the corresponding experiments [80].…”
Section: Importance Of H 2 S For Pathologies Of the Nervousmentioning
confidence: 88%